HEALTHCARE RECEPTION AND HUMANIZED ASSISTANCE IN THE EMERGENCY ROOM FOR ADULTS: NURSES' PERCEPTIONS - Alcides Viana de Lima Neto; Vilani Medeiros de Araújo Nunes; Rafaella Leite Fernandes; Ilcarla Mayara Lopes Barbosa; Gysella Rose Prado de Carvalho (Universidade Federal de Santa Maria, 2013)
http://dx.doi.org/10.5902/217976928279 Aim: to describe the perceptions of nurses that work in the adults emergency room on humanized assistance and healthcare reception and risk classification. Method: it is a descriptive, exploratory and qualitative study carried out through a structured questionnaire and a semi-structured interview with 14 nurses. The sample was composed by nurses mainly women (86%), the average age of 38 years old. The data collected through the interviews was analyzed using the content analysis technique. Results: the data collected was categorized and grouped by similar characteristics, extracting the theme of humanization, the healthcare reception, risk classification and National Policy of Humanization. Final Considerations: the interviewees understand the broader concepts of healthcare reception and humanization, however, the practice depends on the way each professional applies them, transforming this activity into a subjectivity that involves daily work.